2019
DOI: 10.3390/rs11212462
|View full text |Cite
|
Sign up to set email alerts
|

Deep Multi-Scale Recurrent Network for Synthetic Aperture Radar Images Despeckling

Abstract: For the existence of speckles, many standard optical image processing methods, such as classification, segmentation, and registration, are restricted to synthetic aperture radar (SAR) images. In this work, an end-to-end deep multi-scale recurrent network (MSR-net) for SAR image despeckling is proposed. The multi-scale recurrent and weights sharing strategies are introduced to increase network capacity without multiplying the number of weights parameters. A convolutional long short-term memory (convLSTM) unit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…To cope with the speckle noise in SAR images, many noise reduction algorithms have been proposed in the past few years. The classical methods are probabilistic-patchbased (PPB) filter [8], speckle reducing anisotropic diffusion (SRAD) [9], non-local means filter [10,11], total variation model [12], block-matching 3D filtering [13], deep multi-scale recurrent network [14], multilook and refined Lee filtering [15], etc. Zheng et al [16] introduced a SAR change detection method based on PPB filter and k-means clustering model where the PPB filter is used to suppress the speckle noise, and the two difference images are generated by subtraction and log-ratio operators, respectively; then the k-means clustering model is performed on the combined difference image to obtain the final change map.…”
Section: Sar Image Preprocessingmentioning
confidence: 99%
“…To cope with the speckle noise in SAR images, many noise reduction algorithms have been proposed in the past few years. The classical methods are probabilistic-patchbased (PPB) filter [8], speckle reducing anisotropic diffusion (SRAD) [9], non-local means filter [10,11], total variation model [12], block-matching 3D filtering [13], deep multi-scale recurrent network [14], multilook and refined Lee filtering [15], etc. Zheng et al [16] introduced a SAR change detection method based on PPB filter and k-means clustering model where the PPB filter is used to suppress the speckle noise, and the two difference images are generated by subtraction and log-ratio operators, respectively; then the k-means clustering model is performed on the combined difference image to obtain the final change map.…”
Section: Sar Image Preprocessingmentioning
confidence: 99%
“…Take a series of images including three images for example. When we get plenty of feature points in three images, we can get initial matching pointpair based on generic algorithms such as multi-scale edge matching algorithm, shape based matching algorithm and so on [13], [14]. Then we can deduce initial trifocal tensor from Eq.…”
Section: Feature Matching Algorithm Based On Trifocal Tensormentioning
confidence: 99%
“…In the traditional LS method, estimating the phase gradient according to the phase continuity assumption (PGE-PCA) is an essential step. Recent studies [28][29][30][31][32] have indicated that the encoder-decoder architecture based on deep convolutional neural networks (DCNN) can learn the global features from a large number of input images with different levels of noise or other disturbances, which is useful for obtaining the robust phase gradient from noisy wrapped phase images.…”
Section: Introductionmentioning
confidence: 99%